2003
DOI: 10.1063/1.1637429
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs/InP double heterostructures on InP/Si templates fabricated by wafer bonding and hydrogen-induced exfoliation

Abstract: Hydrogen-induced exfoliation combined with wafer bonding has been used to transfer ϳ600-nm-thick films of ͑100͒ InP to Si substrates. Cross-section transmission electron microscopy ͑TEM͒ shows a transferred crystalline InP layer with no observable defects in the region near the bonded interface and an intimately bonded interface. InP and Si are covalently bonded as inferred by the fact that InP/Si pairs survived both TEM preparation and thermal cycles up to 620°C necessary for metalorganic chemical vapor depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 7 publications
0
48
0
Order By: Relevance
“…Wafer bonding and layer transfer has now been applied to semiconductors other than silicon such as Ge, InP, GaAs, and GaN. [2][3][4][5][6] The mechanism of H-induced exfoliation has been extensively studied in the case of silicon, 7,8 and, more recently, in the case of InP. 9 The early work of Weldon et al provided important conclusions: ͑i͒ implantation induced defects serve to trap H within the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Wafer bonding and layer transfer has now been applied to semiconductors other than silicon such as Ge, InP, GaAs, and GaN. [2][3][4][5][6] The mechanism of H-induced exfoliation has been extensively studied in the case of silicon, 7,8 and, more recently, in the case of InP. 9 The early work of Weldon et al provided important conclusions: ͑i͒ implantation induced defects serve to trap H within the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was only recently shown that the concept of hydrogen-induced exfoliation can be applied to the transfer of thin films of InP and GaAs to foreign substrates. [6][7][8] Moreover, a detailed understanding of the role of H in these materials is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 An alternative approach is to employ direct-bonded interconnects between subcells of a multijunction cell, which enables dislocationfree active regions by confining the defect network needed for lattice mismatch accommodation to tunnel junction interfaces. [4][5][6][7][8] We report here a direct-bond interconnected multijunction solar cell, a two-terminal monolithic GaAs/ InGaAs two-junction cell, to demonstrate a proof of principle for the viability of direct wafer bonding for solar cell applications.…”
mentioning
confidence: 99%
“…The wafers were diced into ϳ1 cm 2 area and bonded following the procedure described elsewhere. 8 Special care was taken to keep the surface of the wafers clean of organic contaminations and particles. After degreasing the surface, the native oxide was removed by dipping the GaAs and InP pieces in 7 vol % HCl ͑aq͒ and 10 vol % HF ͑aq͒, respectively, for 30 s. Then the wafers were brought into contact with the ͑011͒ edges aligned.…”
mentioning
confidence: 99%